Hubungan Kecerdasan Emosional Terhadap Stres Kerja dan Pengaruhnya Pada Kinerja Karyawan Apotek Keluarga di Kota Pekanbaru - Elida Gultom (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
This study was conducted at Family Pharmacy in Pekanbaru City with the objective of examining the relationship between emotional intelligence and work stress, as well as their combined effect on employee performance. The research population consisted of all 150 employees in the production department. Using the Slovin formula, a sample of 60 respondents was selected through accidental sampling. Data collection was carried out via an online questionnaire distributed through Google Forms. The analytical methods employed were correlation analysis to assess the relationship between variables and multiple linear regression to measure their simultaneous influence on performance. The results indicated a negative relationship between emotional intelligence and work stress, meaning that employees with higher emotional intelligence tended to experience lower levels of work stress. Furthermore, when examined together, emotional intelligence and work stress had a significant impact on employee performance. Specifically, these two variables contributed 47.4% to the variance in performance, while the remaining 52.6% was influenced by other factors not addressed in this study. The findings highlight the importance of emotional intelligence as a critical factor in managing workplace stress and enhancing performance, especially in the pharmaceutical industry where precision, cooperation, and adaptability are essential. Improving employees’ emotional intelligence may serve as a strategic approach to reducing work-related stress and fostering better performance outcomes. Organizations are therefore encouraged to invest in training and development programs that emphasize emotional regulation, empathy, interpersonal skills, and effective communication. Future research should consider incorporating additional variables such as work motivation, organizational culture, leadership style, and job satisfaction to gain a more comprehensive understanding of the determinants of employee performance. Expanding the research scope to different departments and industries could also provide broader insights into how emotional intelligence and work stress interact across diverse work settings.